Analisis Hidrologi Di Lembangan Sungai Gelugor, Pulau Pinang - Zaini, Masitah (2019)
This study is a study in the field of hydrology consisting of water quality and nutrients. The main objective of this study is to examine the state of river water quality status in the study area. Second, estimating the sediment load and nutrient concentration from the basin entering into the river by monthly and seasonal. Third, identify factors that influence the comparison and correlation between physicochemical character, sediment load and nutrient concentration with discharge. The study was conducted at Sungai Gelugor located at latitude 05 ° 22.379 ° to 05 ° 22.875 ° and longitude 100 ° 17.730 ° to 100 ° 18.654 ° in the State of Penang, Malaysia. Sampling is carried out for 12 months, twice a week on Mondays and Thursdays from 1 January 2016 to 1 January 2017 and during heavy rain season at Station 3 and Station 5. Laboratory analysis is conducted according to the standard procedures recommended by Adams (1989) and APHA (1989). Based on the classification of the National Water Quality Standards for the average temperature (° C), pH, and total dissolved solids (TDS) of the five sampling stations are in class I. While the average oxygen dissolved (DO), in class II and the average turbidity FTU) in class III. The total sediment load discharge recorded at Station 1 is 3455.15 tons / km², Station 2 is 2282.66 tons / km², Station 3 is 2428.86 tons / km², Station 4 is 2043.92 tons / km² and at Station 5 is 1277.84 tons / km². Based on the overall study, the total sediment load discharge recorded in Sungai Gelugor is 1277.84 tons / km² / year.